Socialization of Consumer Protection in Sharia-Based Hotel Services at Hotel Syariah Madani Medan City - Debi Masri; Tina Muhardika Handayani; Munzir Phonna (Outline Publisher, 2026)
This Community Service Program (PKM) aimed to improve the understanding of hotel managers and employees regarding consumer protection in Sharia-based hotel services at Hotel Syariah Madani, Medan City. The program employed a participatory educational approach through observation, interactive lectures, group discussions, case studies, simulations, and question-and-answer sessions. The evaluation of the program was conducted using pre-test and post-test instruments to measure participants' understanding before and after the socialization activities. The results indicated a significant improvement in participants' knowledge of consumer rights, business actors' obligations, transparency in service delivery, complaint handling procedures, and the implementation of Sharia principles in hotel services. The average participant score increased from 62 on the pre-test to 87 on the post-test, demonstrating the effectiveness of the socialization program in enhancing legal awareness and service competence. Furthermore, participants showed greater confidence in applying consumer protection principles to daily hotel operations. This program also encouraged Hotel Syariah Madani to strengthen its standard operating procedures (SOPs), improve complaint management mechanisms, and continuously develop employee competencies in delivering professional, transparent, accountable, and Sharia-compliant services. The program is expected to contribute to improving service quality, increasing customer satisfaction, and supporting the sustainable development of the Sharia hospitality industry.